Pengaruh Strategi Pemasaran Untuk Meningkatkan Penjualan Pada UMKM Warung Mercon Nyak Enni Di Kantin SMK Bina Nusa Mandiri - Marpaung, Eza; Al Qolabi, Ahmad Syamra; Safira, Inayah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
The study focuses on marketing strategies to increase sales at UMKM Mercon Nyak Enni Stall, located in the Bina Nusa Mandiri Vocational School canteen. The research aims to understand the complex business environment and emphasizes the need for businesses to develop strategies that ensure their success and growth. It highlights the importance of strategic planning in business operations, as it enables companies to adapt to changing market conditions. This study aims to analyze the relationship between marketing strategies and business performance, with a particular focus on a SWOT analysis of the company and the factors influencing sales. Additionally, it explores the impact of product quality and distribution on sales in the Mamujú area. The research underscores the need for businesses to adapt their strategies to external factors while maximizing their resources. The findings of this study are expected to inform decision-making regarding marketing strategies and provide recommendations for business development.